Introduction to MCMC methods and the Gibbs sampler - Rossi, Peter (Henry Stewart Talks, 2010)
MCMC methods, Ergodicity, Gibbs sampler, Relative numerical efficiency, Bivariate normal example, A different prior for Bayes regression